Asuhan Keperawatan Pada Ny S Dengan Pemberian Kompres Hangat Daun Kelor Terhadap Nyeri Artitis Gout Di Desa Sungai Rangas Ulu Kecamatan Martapura Barat - Nur Akbar Adi Saputro; Setiawan, Herry (Nerspedia, 2023)
Background: Gout is not a deadly disease, but if not treated properly it can become chronic gout where sufferers will often fellpain in the joints. Based on WHO data, uric acid has a founder of 20% in the world, in Indonesia alone there are 7.30% in tehbanjar area as much as 3.83%. Gout is ranked 4th out of the 10 most common diseases at the UPT Puskesmas Martapura Barat.This is due to high levels of purine compounds, purine compounds themselves can be from offal, canned food and nuts